Analisis F-Score untuk Pendeteksian Window Dressing dengan Moderasi Manajemen Laba dan Cash Holding - Primasari, Niken Savitri; Tri Wahyuningtyas, Endah (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p09, 2021)
Aims to detect financial statements and possibility of window dressing practices with Earning Management and Cash Holding as moderation that will lead to the fraudulent financial statements. The research samples are non-bank companies with  DER value more than 2.00 and included in the kompas 100 index. The final result, indicated no companies conduct window dressing practices of their Performa Past Financial although there are several indicates Manajemen Laba concludes moderation for reduces F-Score that representing the Fraudulent Financial Report. Keywords: Cash Holding; Earning Management; Fraudulent Financial Report; Window Dressing.